The industrial policy of the Republic of Kazakhstan: experience of implementation - Dulambayeva, R.T. (Journal of Economic Research & Business Administration, 2016)
The means of achieving macroeconomic objectives related to improv-ing country`s welfare is the involvement and activation of innovation-in-dustrial component in the overall system reform programs. In this vein, the actual problem is the evaluation of the effectiveness of the industrialization policy. This article describes the problems in implementation of the indus-trialization process in the Republic of Kazakhstan. Research has an evalu-ation of implementation of the State program for accelerated industrial-innovative development of Kazakhstan for 2010-2014. Based on analysis of the implementation of software projects of industrial-innovative devel-opment, in particular the industrial map SPAIID in the old and new version of the main problems and difficulties in the implementation of public poli-cies technologizing national economy. Thus, there is noted the existence of duplication and cumbersome government programs, incompleteness in the definition of target indicators, the absence of personal responsibility for project implementation, high costs of the state financial resources.